Radio-transparent ceramic materials of spodumene-cordierite composition - Zaichuk, A.V.; Amelina, A.A.; Karasik, Y.V.; Khomenko, Y.S.; Lementareva, V.A.; Saltykov, D.Yu. (Functional Materials, 2019)
The paper deals with the processes of obtaining radio-transparent ceramic materials with a complex of high physical and chemical indices. Directional regulation of the ceramics' microstructure and phase composition was carried out by introducing Li₂O-Al₂O₃-B₂O₃-SiO² (LABS) glass into main matrix that consisted of cordierite phase. Optimal composition and temperature conditions for firing of the developed spodumene-cordierite ceramics were established. It is shown that the introduction of LABS glass into experimental compositions contributes to significant intensification of the process of formation of α-cordierite crystalline phase, as well as sintering of ceramic materials obtained. Besides, the product of crystallization of parent glass is β-spodumene which promotes the reduction of CLTE of the obtained ceramic material, on average, to (12.4-17.8)·10⁻⁷ deg⁻¹. The highest indices of mechanical compressive strength (165.8-202.6 MPa) and thermal stability (not lower than 1050 °C) are achieved at the most rational content of LABS glass is 10-20 wt. %. Under this composition the water absorption is within 0.28-0.34 %, apparent density 2.16-2.18 g/cm³, CLTE (16.6-17.8)·10⁻⁷ deg⁻¹. Studies of electrophysical properties of the developed material at the frequency of 10¹⁰ Hz showed that the level of the dielectric constant (ε = 3.8) and dielectric losses (tg δ = 0.0014) spodumene-cordierite ceramics synthesized at reduced temperature of 1300-1350 °C are fully complied with the requirements to the modern radio-transparent materials.